Вплив затоплення вироблених просторів вугільних шахт на зсуви земної поверхні на прикладі шахти «Котляревська» - Сахно, І. Г.; Сахно, С. В.; Петренко, А. В.; Баркова, О. О.; Sakhno, I. G.; Sakhno, S. V.; Petrenko, A. V.; Barkova, O. O. (Донецький державний технічний університет, 2022)
Мета. Дослідження впливу затоплення вироблених просторів лав на активізацію зсувних процесів на підробленій земній поверхні.

Purpose. The study of the influence of mine water rising level of longwalls gob on the activation of deformation processes on the undermined earth's surface.
The influence of ground water level rise in gob of coal mines on ground surface deformation on the example of the Kotlyarevsky mine
Keywords: зсуви земної поверхні; підробка поверхні; мульда зрушень; затоплення шахт; прогноз зсувів; earth's surface displacement; surface undermine, landslides; displacement trough; rise of mine water level; surface displacement forecast